Composite Jackfruit Seed Flour: Impact on the Preferences and Nutritional Value of Almond Crisps - Nafila, Dwita; Saptariana, Saptariana; Ansori, Muhammad; Astuti, Pudji (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
Almond crisps are classified as cookies or pastries that are round and crunchy in texture. Typically, almond crisps are made from wheat flour. However, Indonesia does not produce wheat flour domestically. The average cookie consumption in Indonesia is 0.40 kg per capita per year. To reduce the reliance on wheat flour, it is important to increase the use of local ingredients as alternatives. Jackfruit seeds are a natural resource that remains underutilized. This experimental study formulated almond crisps using a blend of jackfruit seed flour and wheat flour in ratios of 50%:50%, 60%:40%, and 70%:30%. The study aimed to identify differences in consumer preferences and the nutritional content, including calcium, phosphorus, and protein. Data collection methods included subjective assessment, preference testing, objective assessment, and laboratory analysis. The Kruskal-Walli’s test was used for analysis, followed by the Mann-Whitney test to determine preference differences between the various formulations. Results indicated significant differences in taste, color, smell, and texture preferences. Laboratory tests revealed that higher proportions of jackfruit seed flour increased calcium, phosphorus, and protein content. In conclusion, almond crisps made with jackfruit seed flour and wheat flour are nutritious and suitable for all ages, offering a viable alternative to reduce wheat flour use in Indonesia.